Effect of Quantity Factitious Host’s Egg Ratio, Corcyra cephalonica Stainton (Lepidoptera : Pyralidae) and Duration of Ultraviolet Radiation on Parasitization by Trichogramma (Hymenoptera : Trichogrammatidae) - maman kurniawan silaban; suzanna fitriany sitepu; Syahria l Oemry (Jurnal Agroekoteknologi, 2019)
ABSTRACT The aim of this research was to find out quantity of factitious host’s eggs and duration of ultraviolet (uv) radiation which was effective in Trichogramma spp. propagation. This research used completely randomized design factorial with 2 factors. i. e, quantity factitious host’s egg ratio 1 : 6 , 1 : 7,  1 : 8, and 1 : 9 and duration of uv radiation 15 minutes, 25 minutes, and 35 minutes. The result showed that quantity of factitious host’s eggs and duration of uv radiation significantly affected to parasitize of the egg factitious host parasitization emergence and Corcyra cephalonica hatched. The highest percentage of parasitization (95.3%) was in the treatment of 1 : 6 with duration uv radiation 25 minutes, the lowest percentage of larva appeared (19.4%) occured on 35 minutes duration of uv radiation with treatment of 1 : 6, the highest percentage of imago appeared (97%) presented in 25 minutes duration of uv radiation with treatment of 1 : 6. Quantity of the best factitious host’s egg ratio with the best duration of uv radiation was also found in the treatment of 1 : 6 with duration of uv radiation 25 minutes and it was shown from the high percentage of parasitization.Key Words: Corcyyra cephalonica, duration of uv radiation, Trichogramma spp.